PENERAPAN MODEL PEMBELAJARAN INQUIRY DALAM MENINGKATKAN KEMAMPUAN BERPIKIR KREATIF MATEMATIS SISWA - Sitorus, Nurhanifah; Saragih, Sahat (Prismatika: Jurnal Pendidikan dan Riset Matematika, 2026)
This study aimed to improve students’ mathematical creative thinking skills through the implementation of the inquiry learning model. The study employed Classroom Action Research (CAR) conducted in two cycles involving 32 students of class VII-2 at SMP Negeri 2 Pancur Batu. Each cycle consisted of planning, action, observation, and reflection stages. The actions were carried out through inquiry steps, including problem orientation, problem formulation, hypothesis generation, data collection, hypothesis testing, and conclusion drawing. The instruments used were essay tests on mathematical creative thinking and observation sheets. The results showed a consistent improvement in students’ creative thinking skills, indicated by the increase in the average score from 32.38 in the pre-test to 62.50 in cycle I and 87.89 in cycle II, as well as classical mastery improvement from 3.12% to 90.62%. Improvements were also observed in all indicators, namely fluency, flexibility, originality, and elaboration. These findings indicate that the inquiry learning model is effective in enhancing students’ mathematical creative thinking skills and promoting active engagement in learning.